2022
DOI: 10.1155/2022/9953115
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Inflammatory Index in relation to Type 2 Diabetes: A Meta-Analysis

Abstract: Background and Aims. Epidemiologic studies show a strong association between chronic inflammation and type 2 diabetes (T2D). Diet may also affect the risk of T2D by modulating inflammation. This meta-analysis aimed to assess the relation of dietary inflammatory index (DII) and risk of T2D. Methods. PubMed and Scopus were systematically searched from their inception to September 2020 to identify relevant studies. Relative risks, hazard ratios, or odds ratios (OR), with their corresponding 95% confidence interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 98 publications
(138 reference statements)
1
4
0
Order By: Relevance
“…This may be because different studies have differences in the research design, background diseases, types, and quantities of dietary components used to calculate DII, covariate adjustment levels, and most importantly, differences in study quality. However, the theory that dietrelated inflammation may increase the risk of T2DM is consistent with the findings of Motamedi et al [26] . In the stratified analysis of dietary assessment tools, background diseases, and participant gender, DII was not significantly associated with T2DM.…”
Section: And Diabetessupporting
confidence: 90%
See 1 more Smart Citation
“…This may be because different studies have differences in the research design, background diseases, types, and quantities of dietary components used to calculate DII, covariate adjustment levels, and most importantly, differences in study quality. However, the theory that dietrelated inflammation may increase the risk of T2DM is consistent with the findings of Motamedi et al [26] . In the stratified analysis of dietary assessment tools, background diseases, and participant gender, DII was not significantly associated with T2DM.…”
Section: And Diabetessupporting
confidence: 90%
“…Liu [24] believed that the inflammatory response was related to diabetes, and Fu et al [25] pointed out that DII was significantly related to pre-diabetes in older people. A meta-analysis [26] included 48 articles with a total sample size of 1,687,424 subjects. No significant association was observed between DII and the risk of type 2 diabetes mellitus (T2DM) (OR = 1.03, 95% CI: 0.9-1.15).…”
Section: And Diabetesmentioning
confidence: 99%
“…For example, peripheral artery disease (PAD), which is strongly interlinked with inflammation, has been evaluated based on the dietary inflammatory index (DII) [ 176 ]. Consequently, a higher DII score has been associated with poor health and increased risks of obesity, cancer, cardiovascular disease (CVD), chronic obstructive pulmonary disease (COPD), depression, metabolic syndrome, T2D, and kidney stones [ 177 , 178 , 179 , 180 , 181 , 182 , 183 ]. This confirms the value of a diet rich in fibre, folate, and vitamins A, B6, C, and E in alleviating the prevalence of PAD [ 184 ].…”
Section: Obesity-related Complicationsmentioning
confidence: 99%
“…Meanwhile, it was reported that dietary pattern, evaluated by the dietary inflammatory index (DII), was associated with various inflammatory markers, including CRP, IL-6, and homocysteine [12,13]. In addition, higher DII scores have been shown to be associated with poor health and higher risk of diseases, such as obesity [14], various cancer [15,16], cardiovascular disease (CVD) [14,17], chronic obstructive pulmonary disease [18], depression [19,20], metabolic syndrome [21], type 2 diabetes [14,22], and kidney stones [23].…”
Section: Introductionmentioning
confidence: 99%